REVITALISASI PERTANIAN PENGGERAK UTAMA PEMBANGUNAN KAWASAN PERDESAAN DI INDONESIA - Budianta, Aziz (MEKTEK, 2010)
At the implementation of the national development in reformation era, agriculture sectors becomes dominantsector that contributes national income and they are still the major occupation of Indonesian. These sectorsare mainly done in rural areas, therefore, the study of agriculture sectors is dealt with the study of thedevelopment rural areas. The development rural areas is in many aspects, until now, it is relatively less thanit is in the development in urban areas. In developing these sectors, it needs the strategies of therevitalization of agriculture sectors though the application of agro-industry systems, agribusiness, and theintegrated agropolitan concept with the supporting infrastructure